Diagnóstico energético del sistema de suministro eléctrico de la Universidad Técnica de Cotopaxi - Ibujés Zambonino, Andrés Santiago (2017)
Nowadays, the weak planning on the distribution of charges, plus the rapid growth of electricity demand at Technical University of Cotopaxi ("UTC"), has produced a load imbalance into all the phases of the University’s electric system which is out of the established limits of energy regulations. This project aims to develop an energy diagnosis of the energy supply system at the “A” and “B” buildings of the Technical University of Cotopaxi. To identify problems and propose specific solutions; the first stage of this project, the current situation of the university’s electric system was analyzed. Subsequently, measures in the main electrical boards were taken using the Red Fluke 435 Series II analyzer. Through this measurement process, the current electric parameters were identified, and the norms and regulations’ comparison parameters were gotten from the electric data obtained. Also, based on the electrical plans provided by the University, the charge assessment was run which was used to develop the simulation and modeling....